Risk Perception and Adoption of Joint Versus Individual Liability: The Case of Selected Tribes in Tanzania (Global Journal of Management and Business Research, 2015)
Perceive risk is an important factor that influences the adoption intention. Perceived risk associated with the use of microfinance institutions lending model may adversely affect borrowers. Researchers had applied the concept of perceived risk with Technology Acceptance Model (TAM) to measure the use of information technology, but overlooked the use of TAM on microfinance institutions lending models. This study integrates TAM with the adoption of joint vs. individual liability. To address these challenges, a study was conducted from four ethnic groups namely, Gogo, Zaramo, Chagga and Kinga borrowed from PRIDE (T) and FINCA (T). Questionnaires were used to collect information. The Structural Equation Modeling was used to perform the analysis.
Keywords: risk perception; adoption; joint liability; individual liability; tribes; tanzania